Creating concept maps with augmented reality: a case of eclipse of the lunar and solar topic - Ünal Çakıroğlu; Samet Atabaş; Merve Aydın; Ilknur Özyılmaz (The Asia-Pacific Society for Computers in Education (APSCE), 2022)
Abstract Concept maps are the tools used to facilitate meaningful conceptual learning. In this study, an augmented reality (AR)-based concept map (AR-ConMAP) application was developed to facilitate the concept map creation process to overcome the challenges that students face when creating concept maps. The study was carried out as a case study. Observations via using video records and worksheets were used to examine the effect of this application on students' concept map creation skills and their evaluations about their experiences. The results suggested that using AR for creating concept maps provided more accurate results in associating the concept map components and supported students for meaningful conceptual learning. Students evaluated their experiences in using AR also as increasing their sense of enjoyment and curiosity which positively contributed to their motivation to create concept maps. Recommendations for future research and practices were also included.